Ethical dilemmas in psychiatry: When teams disagree. (July 2017) - Silva, Edward; Till, Alex; Adshead, Gwen
Summary: Many ethical dilemmas in medicine are associated with highly unusual clinical situations and are an almost daily challenge for mental health teams. We describe the ethical issues that arose in relation to a significant difference of opinion between team members about using nasogastric clozapine in the treatment of a severely ill patient. We discuss how conflicting emotions and perspectives within teams acquire ethical significance and how negotiation and reflection are essential for good-quality ethical reasoning to take place. Learning Objectives: Understand the different effects and importance of reasoning and emotions in moral decision-making Use a clinical scenario involving a difficult and controversial procedure to explore the impact of social persuasion in moral decision-making Consider the effects of heuristics against rational thinking